Applicability of Visual Arts in the Age of Globalization - Acharya, Bipin (Cognition, 2023)
This research article focuses on the relevance of visual art in the age of globalization. It also depicts the visual culture as an inevitable genre to enhance the humanities through arts. The digitization of arts through technology in terms of painting, photography, film, dance and sculpture is knocking the door of globalization in order to flourish the significance of arts in the modern world. The article varies the arts and other humanities on the basis of their contribution in revealing and reflecting the social norms and values. Similarly, the research moves around the matter of interconnectedness between arts and other humanities since commercialization of arts has created an immediate and superficial satisfaction. It focuses on the ethics of visual culture and the must values it should carry on to reveal in the global world as arts belong to all particular geography or locality equally. The influence of media technology has been a milestone to internalize the visual arts under the umbrella of visual culture. The article explores the significance of the visual culture in the age of globalization whether it serves the humanity through its aesthetic value or not.